Food habits of the smooth dogfish, Mustelus canis, dusky shark, Carcharhinus obscurus, Atlantic sharpnose shark, Rhizoprionodon terraenovae, and the sand tiger, Carcharias taurus, from the northwest Atlantic Ocean - Gelsleichter, James; Musick, John A.; Nichols, Stephanie (Environmental biology of fishes, 1999)
Diet and feeding habits of the smooth dogfish, Mustelus canis, Atlantic sharpnose, Rhizoprionodon terraenovae, dusky, Carcharhinus obscurus, and the sand tiger, Carcharias taurus sharks, were investigated through analysis of stomach contents. Diet in M. canis was relatively homogeneous and was dominated by crustaceans, consisting mostly of rock crabs, Cancer irroratus. Diet in R. terraenovae was more heterogeneous and consisted largely of crustaceans and teleosts, in similar levels of prey importance. Use of cumulative prey curves as a measure of precision indicated that data were insufficient to fully describe the diets of C. obscurus and C. taurus. Nonetheless, these data suggested that both species are generalized feeders and consume a variety of teleost and elasmobranch prey. Further studies are necessary to fully characterize diet in these two species.